2015
DOI: 10.1111/geoa.12107
|View full text |Cite
|
Sign up to set email alerts
|

Thermal bioclimate and climate tourism analysis for odessa, black sea

Abstract: Climate is a main component of nature that, in addition to being a valuable resource, determines the possibility of development of tourism. Apparently, climate and its characteristics determine touristic demand. Choosing a place for vacation or recreation, tourists primarily prefer an optimal climate and weather conditions. Human‐biometeorological resources characterize the connection of climate with a thermal state and health of humans, peculiarities of recreation and health evaluation of the environment. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The results obtained in this study showed that the annual average value of PET in Kyiv is 11.7°C, in Odesa (a big Ukrainian city on the Black Sea shore) is 11.2°C (Katerusha & Matzarakis, 2015), in Szombathely (Hungary) (Gulyás & Matzarakis, 2009) is 13.7°C. The settlements which are located more to the south and characterized by warmer climate, naturally have noticeably higher mean PET values.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The results obtained in this study showed that the annual average value of PET in Kyiv is 11.7°C, in Odesa (a big Ukrainian city on the Black Sea shore) is 11.2°C (Katerusha & Matzarakis, 2015), in Szombathely (Hungary) (Gulyás & Matzarakis, 2009) is 13.7°C. The settlements which are located more to the south and characterized by warmer climate, naturally have noticeably higher mean PET values.…”
Section: Discussionmentioning
confidence: 58%
“…The RayMan model has been broadly applied worldwide in different investigations on human-biometeorology, for instance in Germany (Matzarakis & Endler, 2010), Poland (Błażejczyk & Matzarakis, 2007), Nigeria (Omonijo et al, 2013), Egypt (Hassaan & Mahmoud, 2011), Greece (Matzarakis & Nastos, 2011a), China (Lin & Matzarakis, 2011), Hungary (Gulyás & Matzarakis, 2009), Brazil (Abreu-Harbich, Labaki, & Matzarakis, 2014) and many other places, as well as in Ukraine (Katerusha & Matzarakis, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental resources that are the foundation for tourism/recreation are influenced by weather and climate which also affect the length and quality of tourism and recreation seasons, the health of tourists, and even the quality of tourism experiences (Scott et al, 2004;Katerusha and Matzarakis, 2015;Stojsavljević et al, 2016). Information about climate that is provided to tourists and tourism industry should include not only its general features (mean monthly and annual values of particular climate elements), but also detailed information about thermal comfort as well as aesthetic and physical weather factors (de Freitas, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…PET was used to estimate bioclimatic conditions in different places around the world (e.g., Gulyas et al, 2006;Kovács et al, 2017;Thorsson et al, 2007;Grigorieva and Matzarakis, 2011). Additionally, PET was used to evaluate bioclimatological potential for tourism and recreation in various destinations in different climate zones (e.g., Matzarakis et al, 2013;Katerusha and Matzarakis, 2015;Çalışkan et al, 2011;Brosy et al, 2014;Zaninović and Matzarakis, 2009). The first results of biometeorological parameters in Serbia (Vojvodina, northern part of Serbia) were given by Basarin, et al, (2014).…”
Section: Introductionmentioning
confidence: 99%